Cytomegalovirus seronegativity rate in pregnant women and primary cytomegalovirus infection during pregnancy in rural Germany - Hannah Greye; Thomas Wex; Elina Taneva; Anke Redlich; Serban-Dan Costa; Anke Rissmann (BMC, 2023)
Abstract Background Congenital cytomegalovirus (CMV) infection is the most common congenital infection worldwide and one of the leading causes of congenital hearing loss in newborns. The aim of this study was to determine the seroprevalence rate for cytomegalovirus in pregnant women and the rate of CMV serological testing utilised during pregnancy in a rural region in Germany. Methods Retrospective data on the prevalence of CMV IgG and IgM antibodies were obtained from 3,800 women, identified in the study group of 19,511 pregnant women from outpatient settings whose samples were collected between 1 and 2014 and 30 April 2018. In addition, the serological CMV status in regards to various billing methods was further analyzed. Results Serological CMV tests were performed in 3,800 (19.5%) out of 19,511 pregnant women. 2,081 (54.8%) of these women were CMV seronegative. Among those, seroconversion rate of 0.37-1.42% was identified. A proportion of 2,710 (14.7%) of all 18,460 women with statutory health insurance made use of the CMV testing as an individual health service. Conclusions The low uptake of CMV serological testing in the study population covered indicates low risk awareness among pregnant women and their healthcare professionals. Presented seronegativity rates and routine seroconversion rate, demonstrate importance to improve intervention strategy to prevent feto-maternal CMV transmission.